An Analysis of the National Curriculum Framework for School Education 2023 in the Context of Environmental Education - Shimray, Chong (SCHOOL SCIENCE, 2025)
The much-anticipated curriculum framework for school education—National Curriculum Framework for School Education 2023 (NCF-SE 2023)—was finally brought out in August 2023. Unlike the previous four curriculum frameworks, it is a 600-paged comprehensive document elaborating on different aspects of school education. This article will focus on how Environmental Education (EE) has been envisaged to be implemented in the school curriculum by bringing out the highlights or positive points of the document. It will further explore the possible gaps and challenges that could be encountered by stakeholders in the process of implementation—development of syllabus, resources materials, training modules, etc.—which could come in the way of achieving the aim of EE as laid down in the document. Although the document is final and in public domain for consumption and implementation by stakeholders, the article proposes a framework for EE which has been modified from the one presented in the NCF-SE 2023. The proposed framework, focusing on the curricular goals and competencies, is conceived to be more holistic and simple from the point of view of the stakeholders. The concerns, curricular goals and competencies envisaged for EE in the document has been taken care in the proposed framework